Existence and uniqueness of solution for abstract differential equations with state-dependent delayed impulses - Hernandez, Eduardo; Azevedo, Katia A. G.; Gadotti, Marta C. [UNESP] (Springer, 2019)
We study the existence and uniqueness of mild and classical solutions for a general class of abstract impulsive differential equations with state-dependent impulses. Some examples on partial differential equations are presented.
Keywords: Impulsive differential equation; state-dependent impulses; mild solution; classical solution; analytic semigroup